PELAKSANAAN BUDAYA KERJA ACTIVE PADA ASPEK AKADEMIK DI FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN (FKIP) UNIVERSITAS SEBELAS MARET SURAKARTA - Rima Deswanti; C. Dyah Sulistyaningrum I; Susantiningrum Susantiningrum (Program Studi Pendidikan Administrasi perkantoran FKIP UNS, 2021)
The purpose of this study was to determine: the implementation of an ACTIVE work culture on the academic aspect of FKIP, the implementation of an ACTIVE work culture on the academic aspect of FKIP, solutions to the implementation of a work culture on the academic aspect of FKIP.This research is a qualitative research using a case study approach. Sources of data were obtained from the Vice Dean for Academic Affairs, Head of Study Programs, lecturers, and students. Sampling technique: snowball sampling technique. Data collection techniques: observation, interviews and documents. Data validity test: method triangulation and source triangulation. Data analysis techniques: interactive data analysis techniquesThe results showed that the ACTIVE work culture in the academic aspect at FKIP had been going well, although there were some obstacles. The obstacles faced are the limitations of classrooms and laboratories, the existence of Work from Home (WFH) regulations during the covid-19 pandemic, and the lack of awareness of the ACTIVE work culture. Solutions made: efforts to complete facilities and infrastructure, create innovations during the WFH rule by using alternative media and methods, build awareness by conducting socialization